Cultural influences on the spread of HIV and AIDS - Stageman, Mary (2010)
Abstract Africans, the majority of whom are from sub-Saharan Africa, are the second largest group affected by HIV in the UK. This critical review has looked at the literature about HIV-testing for this group in the UK. The importance of the ‘normalization’ of testing is focused upon and consideration is given to the appropriateness of more community involvement in this process. The problem of stigmatization and lack of confidentiality when accessing HIV-services is also considered. Reasons why people are or are not tested are considered and theories about different health belief models and their relevance to this matter are also considered. Influences upon nurses and how their practice may be altered are outlined. Another conclusion is the need for further research about how best to improve testing rates and how nurses and others can be involved in this process. The state of existing knowledge was determined from both primary and secondary sources. ‘Grey’ literature was also looked at.